Do Inspections Improve Primary School Performance? - Luginbuhl, Rob; Webbink, Dinand; de Wolf, Inge (Educational Evaluation and Policy Analysis, 2009)
This article investigates the effect of Dutch primary school inspections on test scores. These inspections are assessments of the educational quality of schools. The authors use two approaches to estimate the effect of the inspections. The first approach, based on a standard fixed effects model, indicates that inspections lead to slightly better school performance: Test scores increase by 2% to 3% of a standard deviation. However, the fixed effects model might be sensitive to selection bias. The second approach exploits a sample of randomly selected schools originally drawn for the purpose of compiling the annual report of the state of Dutch education. Based on this approach, the authors find that inspections do no harm but seem to have little or no effect on student performance.
Keywords: inspection